Tensions between the Government and the governed in exercising communications rights in Malaysia: The case of online speech - Shuaib, Farid Sufian (2011)
As citizen of the emerging global order, Malaysian – be it the government or the governed – has embraced information communication technology. The government embarks in ambitious project of the Multimedia Super Corridor (MSC) which helps to propel broadband penetration among Malaysian to 56 percent. In ensuring adoption among Malaysian and supports of international industrial players, the government had given the guarantee that there is no censorship in the internet. However, security and public order imperative had compelled the government to reign over internet users for postings and activities the government considered to be detrimental to security and public order such as posting that may incite racial hatred. For the net citizens, such steps amounting to the government reneging on their guarantee of no censorship particularly on political communication. This paper looks at limitations on rights for Malaysian to be involved in the online global communication and criticisms against the limitations. The paper then looks at the need of the net citizens to also consider their duties and ethics in communicating online as a middle path between rights to political communications and duties to communicate responsibly.